Exploring Gotong Simalungun's Approach to Geometry Concepts at SMP Negeri 1 Dolok Batu Nanggar - Parsaulian, Benni Polin; Tambunan, Hardi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research explores the traditional Simalungun carrying culture known as